SMEs Halal Culinary Strategy During The Pandemic Era In South Tangerang - Marissa Grace Haque; Nuraeni; Rifzaldi Nasri (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
The aim of this study is to see and to analyze what type of business strategies should be implemented to the halal-certified culinary SMEs named “Nasi Kebuli Bang Moch.” This study uses mixed-method approaches, equipped with its descriptive analysis. The measuring tool used is a SWOT analysis (strengths, weaknesses, opportunities, threats), through the